Mating Stimulates the Immune Response and Sperm Storage-Related Genes Expression in Spermathecae of Bumblebee (Bombus terrestris) Queen - Guo, Yueqin; Zhang, Qi; Hu, Xiao; Pang, Chunxiu; Li, Jilian; Huang, Jiaxing (Frontiers in Genetics, 2021)
Bumblebee queens have remarkable spermathecae that store sperm for year-round reproduction. The spermathecal gland is regarded as a secretory organ that could benefit sperm storage. Queen mating provokes substantial physiological, behavioral, and gene expression changes. Here, the transcriptomes of spermathecae were compared between virgins and mated queens of the bumblebee, Bombus terrestris L., at 24 hours post mating. Differentially expressed genes were further validated by real time quantitative PCR and immunofluorescence assay. In total, the expression of 11, 069 and 10, 862 genes were identified in virgins and mated queens, respectively. We identified that 176 differentially expressed genes between virgin and mated queen spermathecae: 110 (62.5%) genes were upregulated, and 66 (37.5%) genes were downregulated in mated queens. Most of the differentially expressed genes validated by RT-qPCR were concentrated on immune response (i.e., leucine-rich repeat-containing protein 70 (35.8-fold), phenoloxidase 2 (41.9-fold), and defensin (4.9-fold)) and sperm storage (i.e., chymotrypsin inhibitor (6.2-fold), trehalose transporter Tret1 (1.7-, 1.9-, 2.4-, and 2.4-fold), and heterogeneous nuclear ribonucleoprotein A3 (1.2-, and 2.6-fold)) functions in the spermathecae of mated queens. Procollagen-lysine, 2-oxoglutarate 5-dioxygenase 1 (PLOD1) was hypothesized to promote the mating behavior according to RT-qPCR and immunofluorescence assay. The expression levels of most upregulated immune genes were decreased significantly at three days post mating. In conclusion, the external sperm transfer into spermathecae led to the significantly upregulated immune response genes in bumblebees. These gene expression differences in queen spermathecae contribute to understanding the bumblebee post mating regulatory network.